Adeno-Associated Virus Vector–Based Gene Therapy for Monogenetic Metabolic Diseases of the Liver. Issue 4 (April 2015) - Junge, Norman; Mingozzi, Federico; Ott, Michael; Baumann, Ulrich
Abstract : ABSTRACT: Liver-based metabolic diseases account for a substantial burden of childhood diseases. In most patients, treatment is often limited to supportive measures and liver transplantation is ultimately required. Even despite the excellent long-term outcome of liver transplantation, the procedure is associated with a significant morbidity and mortality. Gene therapy, in contrast, has great potential to save lives, improve the quality of life, and offer few risks and adverse effects compared with present therapies including liver transplantation. The most promising results to date in liver gene transfer have been achieved with adeno-associated virus. Although safety issues, such as immunogenicity of vector and/or transgene product, remain an important concern, gene therapy is ready for clinical trials in adults and adolescents. Developing and testing safe approaches for efficient and long-term stable applications in newborns and small children, such as targeted integration and gene correction, is one of the remaining future challenges.